BVGer D-4916/2020 vom 27. August 2020 - Bundesverwaltungsgericht (2020)
Asyl und Wegweisung (Mehrfachgesuch/Wiedererwägung) | Asyl und Wegweisung (Mehrfachgesuch/Wiedererwägung); Verfügung des SEM vom 27. August 2020